Human-AI Collaboration in Workflow Optimization: A Framework for Hybrid Decision Systems in Automation-Heavy Industries - Rajarshi Tarafdar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive framework for human-AI collaborative workflow optimization in automation-heavy industries, addressing the limitations of fully automated approaches while leveraging the complementary strengths of human judgment and artificial intelligence. We introduce the Collaborative Workflow Intelligence Framework (CWIF), which establishes structured information flows and decision authority boundaries between human operators and AI components across manufacturing, logistics, and financial services domains. Through industry-specific applications, we demonstrate how this collaborative approach enhances production scheduling, quality control, supply chain efficiency, transportation optimization, and financial risk assessment while maintaining appropriate human oversight. Our methodology provides practical guidance for system architecture design, data integration, performance evaluation, and phased implementation, with particular attention to ethical considerations including worker autonomy and skills development. The framework balances operational efficiency with human expertise, creating systems that suggest process improvements and identify inefficiencies while preserving human decision authority in complex and consequential domains. This collaborative paradigm represents a significant advance over traditional automation approaches, offering organizations a path to workflow optimization that enhances rather than replaces human capabilities while addressing the technical, organizational, and ethical challenges of AI implementation.
Keywords: Human-AI collaboration; Workflow optimization; Decision authority boundaries; Adaptive learning systems; Industry-specific automation